2012
DOI: 10.3329/jsr.v4i3.10248
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cobalt Doping in Structural Phase Transition of SmFe<sub>1-x</sub>Co<sub>x</sub>AsO Measured by Low-temperature X-ray Diffraction

Abstract: The parent compound SmFeAsO shows structural phase transition from tetragonal to orthorhombic at the temperature T D = 144 K. In the compound SmFe 1-x Co x AsO, with increasing x the structural transition temperature T D and SDW T N decreases and reaches 0 K at the critical concentration x c . The X-ray diffraction technique has been used here to study the structural phase transition temperature. It is observed that the (400) peak of the parent compound SmFeAsO splits into two peaks (400) and (040)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The 3D structures of human and murine NMPRTs were solved in apoform and in complex with the reaction product NMN. [138][139][140] These data showed that despite a substantial overall similarity with NAPRT, this enzyme is a homodimer. A structural comparison of NMPRT with two other enzyme families suggested that the signature Asp-219 residue of NMPRT is a key determinant of its substrate preference for the amidated form of the pyridine substrate.…”
Section: The Nicotinamide Phosphoribosyltransferasementioning
confidence: 77%
See 1 more Smart Citation
“…The 3D structures of human and murine NMPRTs were solved in apoform and in complex with the reaction product NMN. [138][139][140] These data showed that despite a substantial overall similarity with NAPRT, this enzyme is a homodimer. A structural comparison of NMPRT with two other enzyme families suggested that the signature Asp-219 residue of NMPRT is a key determinant of its substrate preference for the amidated form of the pyridine substrate.…”
Section: The Nicotinamide Phosphoribosyltransferasementioning
confidence: 77%
“…The 3D structure of NMPRT in complex with its potent small-molecule inhibitor APO866 (also known as FK-866) revealed that it binds in a tunnel at the interface of the NMPRT dimer directly competing with the Nm substrate. 138,141 Several other enzymes known to be directly involved in the biogenesis of pyridine mononucleotides via salvage and recycling of pyridines and pyridine nucleosides are less ubiquitous than the three families of phosphoribosyltransferases described above. Here, we briefly describe some of the best-studied salvage enzymes that are captured in Figure 2 and Table 1.…”
Section: The Nicotinamide Phosphoribosyltransferasementioning
confidence: 99%
“…1). In the absence of any structural data 26 which would indicate that our sample is not tetragonal in the thermodynamic equilibrium we assume that the breaking of the 4-fold tetragonal symmetry is not spontaneous, but is a consequence of an external anisotropy such as anisotropic boundary and/or excitation conditions that introduce an anisotropic surface strain. 7 Since in our experiment any external anisotropy must be weak our observations suggest that the intrinsic susceptibility for 2-fold symmetry breaking is large and increases with decreasing T.…”
Section: B Pseudogap and 2-fold In-plane Anisotropymentioning
confidence: 99%